2009
DOI: 10.1007/s00296-009-1157-3
|View full text |Cite
|
Sign up to set email alerts
|

A 2-year comparative open label randomized study of efficacy and safety of etanercept and infliximab in patients with ankylosing spondylitis

Abstract: The signs and symptoms of ankylosing spondylitis (AS) respond inadequately to nonsteroidal antiinXammatory drugs, corticosteroids, and disease modifying antirheumatic drugs in quite a number of patients. Tumor necrosis factor inhibitors have demonstrated to be of value in reducing AS disease activity in clinical trials. The eYcacy and safety of both etanercept and inXiximab in patients with ankylosing spondylitis were compared in a 2-year open label randomised study. Our results are consistent with a signiWcan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 18 publications
7
26
0
3
Order By: Relevance
“…This is demonstrated by the fact that patients with AS have high TNF levels in their sera and inflamed sacroiliac joints 2 3. Moreover, administration of various biologicals blocking TNF,46 significantly reduces disease signs and symptoms. In this regard, we and others have shown that constitutive overexpression of TNF is sufficient to initiate bilateral sacroiliitis with almost all features of AS, including inflammation, bone erosions and cartilage damage 7 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is demonstrated by the fact that patients with AS have high TNF levels in their sera and inflamed sacroiliac joints 2 3. Moreover, administration of various biologicals blocking TNF,46 significantly reduces disease signs and symptoms. In this regard, we and others have shown that constitutive overexpression of TNF is sufficient to initiate bilateral sacroiliitis with almost all features of AS, including inflammation, bone erosions and cartilage damage 7 8…”
Section: Introductionmentioning
confidence: 99%
“…However, some patients with AS do not respond to TNF blocking therapies and others only have minor responses pointing to TNF independent mechanisms of disease 4 5 9. Moreover, at present it is unclear if anti-TNF treatment can prevent the progression of structural damage especially in long lasting disease 10.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous recent and earlier clinical trials have shown that etanercept with its routine administered doses reduces disease activity in those with spondyloarthropathies, including reactive arthritis and ankylosing spondylitis [2][3][4][5][6][7]. According to its proved clinical efficacy and safety, the European League Against Rheumatism recommended this anti-TNF inhibitor for patients with ankylosing spondylitis refractory to conventional treatments [8].…”
Section: Introductionmentioning
confidence: 99%
“…A 2-year randomised open trial reported no differences between infliximab and etanercept therapy with respect to disease activity, lumbar pain, physical function and inflammation [15]. A meta-analysis of randomised controlled trials showed similar results for adalimumab, etanercept and infliximab, and further analysis applying a mixed treatment comparison corroborates this evidence, as well as observational cohort studies [16–20].…”
Section: Discussionmentioning
confidence: 83%